EKSISTENSI GOFOOD DAN SHOPEEFOOD DALAM PERKEMBANGAN UMKM DI KELURAHAN GEGERKALONG, KOTA BANDUNG - Maharani, Nazwa; Oktaviani, Indri; Teguh, Mutiara Ramadhania; Hamdani, Yusuf; Firmansyah, Buyung (Universitas Budi Luhur, 2024)
The business landscape has changed greatly due to advances in digital technology, especially in the Micro, Small and Medium Enterprises (MSME) sector. MSME players are able to access a wider market with the help of online platforms such as GoFood and ShopeeFood. This research was conducted with the aim of describing the benefits of GoFood and ShopeeFood existence for MSME in Gegerkalong Village, Bandung City. The qualitative descriptive analysis method was used to collect data by interviewing MSME owners who use the GoFood and ShopeeFood distribution platforms. The results showed that the presence of these services had a significant positive impact on the income and business development of MSMEs. In addition to increasing sales volume, these services play an important role as an effective promotional tool. MSME players also experienced other benefits, such as ease in the delivery process, the ability to focus on important aspects of the business, and an increase in the popularity of their business. However, there are obstacles to overcome, such as rising commission costs and dissatisfaction on the part of drivers. The results of this study provide a more detailed understanding of the positive contributions of GoFood and ShopeeFood services and the constraints faced by MSME players, strengthening the understanding of the importance of food delivery services in supporting the growth and development of MSME businesses. It can be concluded that the data collected from MSME players in Gegerkalong Village, Bandung City, shows the existence of GoFood and ShopeeFood can help develop MSME businesses and increase their income and MSME players can reach consumers outside the area with these platforms.Lanskap bisnis kini sangat berubah karena kemajuan teknologi digital, terutama di sektor Usaha Mikro Kecil dan Menengah (UMKM). Para pelaku UMKM mampu mengakses pasar yang lebih luas dengan bantuan platform online seperti GoFood dan ShopeeFood. Penelitian ini dilakukan dengan tujuan untuk mendeskripsikan manfaat eksistensi GoFood dan ShopeeFood bagi UMKM di Kelurahan Gegerkalong, Kota Bandung. Metode Analisis deskriptif kualitatif digunakan untuk mengumpulkan data dengan mewawancarai pemilik UMKM yang menggunakan platform distribusi GoFood dan ShopeeFood. Hasil penelitian menunjukkan bahwa kehadiran layanan tersebut memberikan dampak positif yang signifikan terhadap pendapatan dan perkembangan bisnis UMKM. Selain meningkatkan volume penjualan, layanan ini berperan penting sebagai alat promosi yang efektif. Para pelaku UMKM juga merasakan manfaat lain, seperti kemudahan dalam proses pengiriman, kemampuan untuk fokus pada aspek penting bisnis, serta peningkatan dalam popularitas usaha mereka. Namun, ada kendala yang harus dihadapi, seperti kenaikan biaya komisi dan ketidakpuasan dari pihak pengemudi. Hasil penelitian ini memberikan pemahaman yang lebih rinci tentang kontribusi positif layanan GoFood dan ShopeeFood serta kendala yang dihadapi oleh para pelaku UMKM, memperkuat pemahaman tentang pentingnya layanan pengiriman makanan dalam mendukung pertumbuhan dan perkembangan bisnis UMKM. Dapat disimpulkan bahwa data yang dikumpulkan dari para pelaku UMKM di Kelurahan Gegerkalong, Kota Bandung, menunjukkan eksistensi GoFood dan ShopeeFood dapat membantu mengembangkan usaha UMKM dan meningkatkan pendapatan mereka serta para pelaku UMKM dapat menjangkau konsumen di luar daerah dengan platform ini